Exploration and documentation of ethnobotanicals used by traditional healers from Purulia district of West Bengal, India - Tulika Bhattacharjee, Ghanashyam Mahato, Nilanjana Banerjee (Journal of Applied Pharmaceutical Science, 2024)
Traditional healers of the Purulia district use their traditional knowledge in ethnomedicine for the treatment of several human ailments. The main objective of this investigation is to gather information on medicinal plants used to treat various ailments by local inhabitants of the Purulia district and document them in digitized form. All the information such as various doses, methods of formulations, and modes of administration were recorded along with the local name, family, plant parts used, and short profile of information on the basis of semi semi-structured questionnaire and focus group discussions. A total of 51 herbal plants under 34 families are used by the informants either as a mono-herbal drug or polyherbal drug to treat various ailments. The most commonly used plant part is the leaf followed by the root, whole plant, flower, fruit, bark, bulb, latex, stem, and rhizome. These plant parts are used to treat dermatological problems, general health problems, abdominal problems, and ear, nose, and throat problems. Ethnobotanical data was analyzed using appropriate statistical methods such as use value and fidelity level. Hence, this could be summarized that collected ethnobotanical information on therapeutic plants of the Purulia district was documented in digitalized form for knowledge preservation for further studies on them as well as by pharmaceutical industries.
Keywords: Ethnomedicine, fidelity level, Purulia district, tribal people, use value